2018
DOI: 10.1130/l1037.1
|View full text |Cite
|
Sign up to set email alerts
|

Towards a clarification of the provenance of Cenozoic sediments in the northern Qaidam Basin

Abstract: Determining the provenance of sedimentary basin fill in the northern Qaidam Basin is a key step toward understanding the sedimentary system dynamics and mountain-building processes of the surrounding orogenic belts in Tibet. The exceptionally thick (average of 6-8 km) Cenozoic fluvio-lacustrine deposits in the northern Qaidam Basin were once thought to have been eroded from the nearby northern Qaidam Basin margin and the southern Qilian Shan and to reflect the prolonged thrust-related exhumation of these oroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 80 publications
3
24
0
Order By: Relevance
“…Compared with the widespread middle Miocene deformation across the entire Qilian Shan, the early Cenozoic deformation is just reported south of the Qaidam Basin (e.g., Clark et al, ; Jolivet et al, , ; D. Liu, Li, et al, ; Mock et al, ; F. Wang, Shi, et al, ; Y. Wang et al, ; Yin et al, ), the northern Qaidam Basin (e.g., F. Cheng et al, ; He et al, ; Jolivet et al, ; Lu et al, ; Yin et al, ; Zhuang et al, ), and parts of the Qilian Shan, such as the Xining‐Lanzhou Basin (Dupont‐Nivet et al, ; Dai et al, ; J. Zhang et al, ; Wang, Zhang, Liu, et al, ), western Qinling (Clark et al, ; Duvall et al, ), and the central‐northern Qilian Shan (e.g., Qi et al, ; He et al, ; Figure b). The Paleocene‐Eocene and widespread middle Miocene deformation suggest that the crustal shortening has extended into the northern Tibetan Plateau to reactive preexisting weaknesses shortly after the India‐Eurasia collision, followed by a phase of extensive crustal shortening across the Qilian Shan since the middle Miocene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the widespread middle Miocene deformation across the entire Qilian Shan, the early Cenozoic deformation is just reported south of the Qaidam Basin (e.g., Clark et al, ; Jolivet et al, , ; D. Liu, Li, et al, ; Mock et al, ; F. Wang, Shi, et al, ; Y. Wang et al, ; Yin et al, ), the northern Qaidam Basin (e.g., F. Cheng et al, ; He et al, ; Jolivet et al, ; Lu et al, ; Yin et al, ; Zhuang et al, ), and parts of the Qilian Shan, such as the Xining‐Lanzhou Basin (Dupont‐Nivet et al, ; Dai et al, ; J. Zhang et al, ; Wang, Zhang, Liu, et al, ), western Qinling (Clark et al, ; Duvall et al, ), and the central‐northern Qilian Shan (e.g., Qi et al, ; He et al, ; Figure b). The Paleocene‐Eocene and widespread middle Miocene deformation suggest that the crustal shortening has extended into the northern Tibetan Plateau to reactive preexisting weaknesses shortly after the India‐Eurasia collision, followed by a phase of extensive crustal shortening across the Qilian Shan since the middle Miocene.…”
Section: Discussionmentioning
confidence: 99%
“…It is also supported by provenance analyses for the Qaidam Basin, which indicate that early Cenozoic sediments in the northern Qaidam Basin were shed from the Kunlun Shan rather than the southern Qilian Shan, and provenance change occurred during early‐middle Miocene (Bush et al, ; W. Wang, Zheng, Zhang, et al, ). While Lu et al () suggest that Bush et al () may misidentify the underlying Cretaceous Quanyagou formation as the lower part of the Lulehe formation such that produce improper conclusions, they concluded that the Lulehe formation is characterized by proximal alluvial fan deposits that originated from the northern Qaidam Basin and the southern Qilian Shan based on evidence of sedimentology, facies analysis, and seismic reflection profiles (e.g., F. Cheng et al, ; Lu et al, ; Yin et al, ). Cheng et al () suggest that if both the traditional (~50 Ma) and younger (~25.5 Ma) age models are correct, the Qaidam Basin may experience diachronous basin‐fill process and the lithostratigraphic units throughout the basin are time transgressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from previous studies supports the early Cenozoic tectonic exhumation event. Adjacent to the Qilian Shan, the northern Qaidam Basin and the Jiuquan Basin also archive detritus with distinct AFT ages of ~60–50 Ma (He et al., 2017, 2018; Jian et al., 2018; Lin et al., 2019); the deposition of coarse clasts that originated from the Qilian Shan overlying the Cretaceous in unconformable prevail in the northern Qaidam Basin (Ji et al., 2017; Lu et al., 2018; Zhuang et al., 2011), accompanied by the beginning development of synsedimentary thrusting structures and deformation during the Paleocene‐early Eocene (Cheng et al., 2019; Yin et al., 2008); analogously, coarse clast‐dominated sediment rapidly accumulated over the Cretaceous in unconformable in the Xining Basin during the early Eocene (Fang et al., 2019). Early Eocene initiation of rapid exhumation of several terranes in the southern Qilian Shan (Jian et al., 2018; Qi et al., 2016; Cheng et al., 2016; Zhuang et al., 2018) and the northern extension of the Qilian Shan (An et al., 2020) has been revealed by thermochronology.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous approaches have been applied to provenance analysis in the Qaidam Basin, including clast composition of conglomerate [1][2][3], sandstone modal analysis [4][5][6][7], detrital mineral U-Pb geochronology [8][9][10][11][12][13], paleocurrent analysis [3,4,[10][11][12][13], heavy mineral analysis [4,5,[14][15][16], and element geochemistry [7,17], etc. However, some discrepancies still exist in previous results of provenance analysis.…”
Section: Introductionmentioning
confidence: 99%